2009
DOI: 10.1177/001440290907600104
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Transition-Related Strengths and Needs of Adolescents with High-Incidence Disabilities

Abstract: Although meaningful assessment is considered the cornerstone of transition planning, little empirical guidance is available to inform this assessment process. This study examined the transition-related strengths and needs of 160 students with emotional and/or behavioral disorders (EBD) or learning disabilities (LD) from the perspectives of special educators, parents, and youth. Teachers rated youth with EBD as evidencing more substantial needs than youth with LD across all 9 planning domains. Student's ratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…However, youth self-reports in certain skill domains are not always consistent with reports from other key adults in their lives. Previous research has found that at-risk youth reported higher skills in behavior and social competence domains than their parents and teachers (Carter et al 2009;Hoza et al 2004;Owens et al 2007). These recommended transition assessment practices allow service providers to create individualized transition plans that promote successful reintegration into the community.…”
Section: Protective Factorsmentioning
confidence: 95%
See 3 more Smart Citations
“…However, youth self-reports in certain skill domains are not always consistent with reports from other key adults in their lives. Previous research has found that at-risk youth reported higher skills in behavior and social competence domains than their parents and teachers (Carter et al 2009;Hoza et al 2004;Owens et al 2007). These recommended transition assessment practices allow service providers to create individualized transition plans that promote successful reintegration into the community.…”
Section: Protective Factorsmentioning
confidence: 95%
“…First, research suggests that transition assessment should include multiple perspectives from individuals who know the youth well across different contexts (Carter et al 2009). Considering many youth in care have limited social support networks and often experience multiple previous placements (Connor et al 2004;Courtney and Heuring 2005), identifying individuals who can provide an accurate and current evaluation of these skills can be difficult.…”
Section: Protective Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The post-school outcomes of youths with special educational needs have long been considered a revealing barometer of the quality and effectiveness of special education (for example, Carter, Trainor, Sun & Owens, 2009.) Unfortunately, findings from earlier studies and meta-analyses indicate that, as a whole, special education fails to prepare such youths to compete for positions in secondary education and working life (Newman, Wagner, Cameto & Knokey, 2009;Reid, Gonzalez, Nordness, Trout & Epstein, 2004).…”
Section: Introductionmentioning
confidence: 99%